2020
DOI: 10.1002/jpln.202000151
|View full text |Cite
|
Sign up to set email alerts
|

Boron and zinc fertilizer applications are essential in emerging vegetable‐based crop rotations in Nepal

Abstract: Background: Since recently, the traditional rice–wheat rotation systems in Nepal are subject to drastic changes. Progressing urbanisation and shifting consumer preferences drive a replacement of wheat by high‐value vegetables during the cold dry season, particularly in the peri‐urban fringes, while emerging water shortages prevent permanent soil flooding during the monsoon season, leading to partial substitution of lowland rice by less water‐consuming upland crops. Associated changes in soil aeration status af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…At the same time, Zn uptake was higher in non‐fertilized maize grown in soils with prior tomato and wheat cultivation, compared to cauliflower. These results are fully in line with the known high Zn demand of cauliflower ( Singh et al, 2012), and the previously observed lower Zn uptake by wheat and tomato compared to cauliflower ( Shrestha et al, 2020b).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…At the same time, Zn uptake was higher in non‐fertilized maize grown in soils with prior tomato and wheat cultivation, compared to cauliflower. These results are fully in line with the known high Zn demand of cauliflower ( Singh et al, 2012), and the previously observed lower Zn uptake by wheat and tomato compared to cauliflower ( Shrestha et al, 2020b).…”
Section: Discussionsupporting
confidence: 90%
“…It should be kept in mind that cauliflower, which is known to have a rather high B requirement ( Kotur , 1991), received here a total of 4.4 kg B ha −1 compared to 2.2 kg B ha −1 for tomato. The relatively low amounts of B applied to tomato were largely absorbed by the crop ( Shrestha et al, 2020b), leaving little residual B left in the soil for inducing possible carry‐over effects in maize. On the other hand, more B was left in the soil after wheat (with a very low B demand: Gupta , 2007; Wimmer et al, 2015) and cauliflower (with a larger supply), which could be taken up by the follow‐up maize in the Fluvisol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations